Shariah governance reporting of Islamic banks: An insight from Malaysia - Tasya Aspiranti; Qaisar Ali; Oktofa Yudha Sudrajad; Sulistya Rusgianto (Cogent Business & Management, 2023)
This study examines the shariah governance reporting (SGR) of Islamic banks (IBs) through a reporting index comprised of six dimensions, namely shariah committee, shariah review, shariah audit, shariah risk, overall transparency, and investment account holders. The data between 2014-2018 werecollected from the annual reports of 16 licensed IBs in Malaysia and was analyzed using the content analysis technique to gain insight into SGR practices. The empirical results indicate that sampled IBs have reported above average (60%) information of shariah governance (SG) and overall dominance of shariah reporting across the index. The segmental overview of SGR represents that all six dimensions were reported in a scattered pattern, while thematic reporting was less scattered. Broad spectrum results indicate that Malaysian IBs have reported above average (62.22%) information about shariah review and shariah risk (71.11%), whereas other dimensions' reporting was below average. The findings have also confirmed that the SGR of IBs is statistically different. This research offers matrices for IB managers to determine the accuracy, validity, and authenticity of their annual reports and customize according to shariah reporting requirements. The regulators may use this study to assess IBs' compliance with SG and improve their regulations as per globally accepted governance standards.
Keywords: 650; Islamic banks; shariah governance index; Islamic financial reporting; shariah governance; sharia reporting